Environmental Kuznets Curve (EKC): Implications on Economic Growth, Access to Safe Drinking Water and Ground Water Utilisation in India (Global Journal of Human-Social Science, 2015)
It is very tough trade-off between economic growth and environmental sustainability in a faster growing developing country like India. The Environmental Kuznets Curve (EKC) hypothesis proposes that environmental degradation initially increases with the income rise, and then begins to decrease once a certain threshold of income growth is achieved. The present study is an endeavour to explore EKC in relation to safe drinking water access, groundwater resource development and utilisation, as well as its correlation with waterborne diseases in 32 Indian States/Union Territories (UTs) within a period of 11 years, 2001-2012. Results from the panel analysis reveal that no EKC relationship exists with the considered indicators in the Indian context. Furthermore, income growth is observed to present no significant effect on all of the considered indicators. Income growth in lower-income States/UTs immensely helps to improve the access to safe drinking water compared to the higher-income States/UTs. Rapid expansion of irrigated agriculture and obsolete abstraction regulation tactically allows overexploitation of the groundwater resource.
Keywords: environmental sustainability; economic growth; environmental kuznets curve (ekc); safe drinking water access; ground water; waterborne diseases